A case of atypical systemic primary carnitine deficiency in Saudi Arabia - Abdulrahman Alghamdi; Hani Almalki; Aiman Shawli; Rahaf Waggass; Fahad Hakami (MDPI AG, 2018)
Systemic primary carnitine deficiency (SPCD) is an autosomal recessive inborn error of fatty acid metabolism caused by a defect in the transporter responsible for moving carnitine across plasma membrane. The clinical features of SPCD vary widely based on the age of onset and organs involved. During infancy, patients might show episodes of hypoketotic hypoglycemia, hepatomegaly, elevated transaminases, and hyperammonemia. Skeletal myopathy, elevated creatine kinase, and cardiomyopathy are the main manifestations in children with SPCD, while in adults, the disorder is usually manifested as cardiomyopathy, arrhythmias, or fatigability. Here, we report a 5-year-old boy with SPCD that presented as dilated cardiomyopathy with atypical features, such as anemia, respiratory distress, and proximal muscle weakness. This report supports considering carnitine deficiency treatment in the work-up of unexplained pediatric dilated cardiomyopathy.